El juego de pelota y el derecho público - Juan Antonio Ureña Salcedo (Revista Vasca de Administración Pública)
Public law is closely linked to the game of pelota. In the historical review that we make in the first pages of this work, after a brief description of pelota in Greece and Rome, the Oath of the Jeu de Paume occupies a prominent place. The reader will also find historical references to the interferences of the political power through prohibitions, the public regulation of betting and the monopolistic exploitation, by means of privileges, of the game in trinquettes. The work continues with some current legal issues related to pelota a mano. The distribution of competences is succinctly addressed, the disconnection between the Basque Federation of Pelota and the Valencian Federation of Pilota is pointed out, and classic issues such as betting and liability for damages are in sisted on. The study ends, after recalling the declaration of Valencian pilota and other modalities as goods of intangible cultural interest, arguing for the deserved recognition of the game of pelota, without gentiles, as intangible cultural heritage of humanity.